Analisis Kesulitan Siswa pada Materi Pecahan - Unaenah, Een; Rohmah, Nafisah Nur; Sefani, Nur Aliza (Lembaga Yasin AlSys, 2023)
This study aims to find out whether learning simple fractions in this elementary school students are able to solve simple fraction questions and understand the basic concepts of simple fractions and ascertain whether there are difficulties students experience in solving simple fraction problems. This type of research is descriptive qualitative. The object of this study was to interview several teachers and students covering simple fractions in grade 5. The data collection methods used were analysis, interviews, tests, and documentation. he results of the students' workmanship test were used to collect data related to the difficulties students had when working on math problems on fraction material where the difficulty of the test was an indication of a lack of understanding of the concept of fractions. As for interview guidelines for teachers. The purpose of interviewing teachers is to find deeper information about mathematics learning activities on fractions and mistakes that students often make in solving problems about fractions.